Is Social Capital Important in Development (Indonesia Macro Analysis) - Prince Charles Heston Runtunuwu; Muhammad Kamal (Jurnal Mantik, 2021)
The new paradigm development is not only measured from the economic aspect through Gross Domestic Product (GDP), but also viewed multidimensional from the change of social structure, behavior, and national institution. Such social perspective is called social capital. Social capital is considered an important determinant of economic development. so that social capital is placed as one input in development. The purpose of this scientific paper is to analyze the influence of social capital in economic development with the approach of Gross Regional Domestic Product (PDRB) in 33 Provinces in Indonesia. The analysis of the effect of social capital on PDRB along with other variables such as physical capital, labor, and human capital is done at the macro level. The limits are the role of social capital in 2017 and 2019 due to data availability. The result of research indicates that social capital has not enough to influence human capital at macro level, while human capital has significant effect to Gross Regional Domestic Product (PDRB). It can say that social capital indirectly is no effected on GRDP in Indonesia.